Becoming a Science Activist: A Case Study of Students' Engagement in a Socioscientific Project - Eran Zafrani; Anat Yarden (Universidade de Lisboa, 2017)
Abstract Complications arising from socioscientific issues (SSI) call for immediate and responsible action and warrant students' activism on science-related issues. These issues therefore provide a solid learning context for the advancement of responsible research and innovation (RRI) in science education. This study investigates the development of students' identities as activists as they participate in a high-school project aimed at resolving the problem of global hunger. Drawing from practice-linked identity theory, we present the narratives of two students to examine how they came to embrace the identity of activist. Findings indicate that the students' identities as activists were supported through participation in highly contextual and emotionally charged experiences and through the ability to fill roles that were perceived as integral and authentic to the students. We discuss the potential of a well-structured activity to assist students in deeply engaging with responsible actions. resumo As complicações que advêm das questões sociocientíficas requerem ações imediatas e responsáveis e uma garantia de ativismo estudantil em questões relacionadas com a ciência. Estas questões fornecem, assim, um contexto de aprendizagem sólido para o avanço de uma Investigação e Inovação Responsáveis (IIR) em educação em ciências. Este estudo investiga o desenvolvimento da identidade dos estudantes como ativistas ao participarem num projeto da escola secundária destinado a resolver o problema da fome global. Com base numa teoria da identidade, ligada à prática, apresentamos as narrativas de dois estudantes, para analisar a forma como eles adotaram a identidade do ativista. Os resultados indicam que a identidade dos estudantes como ativistas fundamenta-se na participação em experiências altamente contextuais e carregadas de emoção e na capacidade para desempenhar papéis que foram percebidos como autênticos e íntegros pelos estudantes. Discutimos o potencial de uma atividade bem estruturada para ajudar os alunos a envolverem-se profundamente em ações responsáveis.